Contemporary perspectives on reading and spelling [ - Connelly, Vincent; Wood, Clare Patricia (New perspectives on learning and instruction, 2009)
With contributions from leading international researchers, this book offers a critique of current thinking on the research literature into reading, reading comprehension and writing